Human resources management in domestic agricultural enterprises - Carić Marko; Prodanović Radivoj; Khoja Amina Hamina A.; Gardašević Jovana (Ekonomija: teorija i praksa, 2022)
The aim of this paper is to identify key human resource management activities in domestic agricultural enterprises and their scope, as well as accompanying problems. The research used a quantitative method, ie. a written structured survey was conducted via the Internet. The survey included 64 companies, and 29 or 43% responded. The results of the research show that domestic agricultural companies mainly carry out human resource management activities. In 17% of companies, a professional manager is hired, while in most directors they are superior to employees. Furthermore, the research found that most attention is paid to rewarding, motivating, training employees and managing safety at work, while job evaluation, socialization, cooperation with educational institutions and measuring employee satisfaction are of secondary importance. Personnel problems such as low motivation, work discipline, disturbed interpersonal relations, employee turnover, engagement of seasonal workers and lack of interest in training were expressed. An effective personnel policy can prevent staffing problems and improve productivity. We advise companies to consider investing in a quality manager, who would deal exclusively with human resources.